PICOLEARN: WEB-BASED LEARNING MEDIA DEVELOPMENT ON PRIMM APPROACH TO ENHANCE COGNITIVE PROCESS IN PROGRAMMING - Gustin, S. Sarah Nuraisya; Junaeti, Enjun; Arianti, Andini Setya (Research and Development Journal of Education, 2025)
The Merdeka Curriculum emphasizes the attainment of Higher-Order Cognitive Processes. However, achieving these cognitive goals remains a significant challenge, particularly in programming education. This study focuses on the development and evaluation of PICOLEARN, a web-based learning platform utilizing the PRIMM (Predict, Run, Investigate, Modify, Make) approach to enhance students' cognitive processes in looping structure control programming. The research was conducted in Bandung, Indonesia, involving 35 vocational high school (SMK) students as participants. The object of the study was the learning of looping structures, a fundamental topic in programming. The learning media was developed following the ADDIE model, beginning with a needs analysis and culminating in the design of instructional materials, questions, and learner activities. The media was validated by experts, achieving an 81% feasibility score, classifying it as "very good" for use. The effectiveness of the learning media was assessed using a normalized gain (n-Gain) test, which showed an average increase of 0.40 across all class groups, indicating moderate improvements in students' cognitive abilities. The results highlight the potential of the PRIMM approach to support cognitive development in programming learning. Furthermore, student responses to the media, measured by the the Technology Acceptance Model (TAM), resulted in an average score of 76%, reflecting a positive reception. The findings demonstrate that PRIMM-based learning media is both effective in enhancing cognitive processes and well-received by students. However, further refinements are recommended to maximize its impact on learning outcomes.